Influence of Tourism on Income Inequality in Transitional Economies: Does Foreign Direct Investment Matter? - Tsaurai, Kunofiwa (EuroEconomica, 2022)
This study investigated the impact of tourism on income inequality in transitional economies using panel data analysis methods, namely fixed effects, fully modified ordinary least squares (FMOLS), dynamic generalised methods of moments (GMM), pooled ordinary least squares (OLS) with data ranging from 1999 to 2019. The influence of the complementarity between tourism and FDI on income inequality in transitional economies was also investigated. There is no agreement in the literature regarding the influence of tourism on income inequality. The available literature on the subject matter produced results which lacks conclusiveness, are divergent and mixed, hence prompting the author to undertake this study to fill in the glaring gaps in the literature. To a large extent, the study observed that tourism, foreign direct investment, the complementarity effect, employment, human capital development, infrastructural development and information and communication technology significantly reduced income inequality in transitional economies. Transitional economies should develop and implement policies that are geared at enhancing tourism, employment, infrastructural development, foreign direct investment inflows, and human capital development and information and communication technology to reduce income inequality. Further studies should estimate the minimum threshold level of tourism above which significant income inequality reduction occurs.